Spa attributes, customer satisfaction and retention: customers of 4 & 5 stars hotel spas in Kuala Lumpur / Nor Laily Ibrahim - Ibrahim, Nor Laily (2010)
Malaysian society nowadays is veering into health and healthy living. A spa is considered as the closest means to relax and unwind from the hectic daily schedule. Due to this fact, hotels are trying to tap into the potential that a spa has to offer by providing spa facilities to their customers. However, spa hotels have not only other spa hotels to compete with; they would also have to put independent into the equation. The competition is further aggravated by the current economic condition that forces individuals to reprioritize their spending behaviour. This study looks into assessing the growth factor of hotel spas (reason customer frequents a hotel spa) and the relationship between hotel spas attributes, customer satisfaction and customer retention in 4 & 5-stars hotel spas. A total of 188 hotel spa users in 4 and 5 stars spa hotels in Kuala Lumpur participated in this research. The data were collected using questionnaires that were distributed within the customers of 4 & 5-stars hotel spas in the Kuala Lumpur city area. The Pearson’s Correlation analysis was then used in determining the existence of relationship among the three variables used based on the adaptation of the SQIP approach. It is later shown that the hotel spa attributes are correlated to both customer satisfaction and retention respectively and that the service, quality, image and price should be taken into serious consideration in the attempt of retaining existing customers of a 4 & 5-stars hotel spas in Kuala Lumpur.